Pathfinders or Explorers: Student teachers' ways of handling the challenges of classroom management in a simulation - Marcus Saumellson (University of Aberdeen, School of Education, 2018)
Twenty-three Swedish student teachers volunteered to try to handle ordinary and difficult challenges of classroom management in a realistic, hypertext-based computer simulation. The point of departure for constructing this simulation was international classroom management research. The simulation offered the students an opportunity to choose from authoritarian, authoritative, democratic, and abdicated leadership styles as approaches to handling six teaching sequences. The results of the test showed that on the one hand, the students shifted between different leadership styles during the test, but on the other hand, that they used either a pathfinder or an explorative approach while doing so. Pathfinders acted as if they were searching for the shortest and fastest way through the simulation; while explorers looked into more or less all the options presented. Also shown was that none of them used the same leadership style to handle ordinary or difficult challenges. Almost all of the students used the authoritative and democratic leadership style, which could be understood as them (a) recognizing the greater validity of these two leadership styles, and therefore eliminating extremes like the authoritarian and abdicated ones, (b) selecting authoritative and democratic choices to reflect what they themselves experienced as pupils in school and as students during their practice teaching and (c) perceiving that these leadership styles are close to an ideal for the way they want to perform as teachers as soon as they start working.